Measurement of Athletic Physical Activity In 100-meter Sprint Running Numbers In Students - Luthfiyah Syaharani; Hartati Hartati; Silvi Aryanti (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to determine the results of measuring athletic physical activity in the 100-meter running number. This type of research is descriptive, using a quantitative approach and using percentage data analysis. The sample used was all students of class VII, totaling 70 students. The instrument in this study used a test that measures physical activity in the 100-meter run by measuring speed (100-meter run), endurance (1000-meter/800-meter run), strength (sit ups and push ups), and flexibility (sit and reaches). Data analysis techniques were processed by using normality and percentage tests using computer assistance (excel) and the SPSS 22 program. Based on the analysis of the percentage of data obtained from the results of physical activity running the 100-meter run, this is in a good category with a result of 60.2%. By getting each result that is for speed 70%, endurance 41%, strength 80%, and flexibility 50% the average yield is 60.2% in the good category. The results of this study imply that even if the results of measuring physical activity in the 100-meter run are good, then the results of the speed in the 100-meter run will be good and can support the daily activities carried out by students.